Materiale Textkulturen. Konzepte-Materialien-Praktiken - Sauer, Rebecca; Ott, Michael R.; Meier, Thomas (De Gruyter, 2021)
How does one define and explore the “material presence of the written in non-typographical cultures?” The interdisciplinary and collaborative essays in this handbook present theoretical principles, describe text-bearing materials and objects, and investigate the diverse practices related to text-bearing artifacts. The analysis is illustrated with examples drawn from a period of over 4,500 years.